Resilience For Whom? An analysis of socio-political factors shaping adaptive capacity of coastal fishing communities in northern Norway - Moors,Marietta (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
Arctic coastal fishing communities face rapid environmental, social, and regulatory changes that challenge their adaptive capacity and resilience. Focusing on Moskenes on the Lofoten islands in northern Norway and approaching the case with a critical perspective on social resilience theory, this study investigates the adaptability of coastal fisheries and how their adaptive capacity is affected by socio-political factors. By conducting interviews and a document analysis, the findings highlight the prioritization of economic efficiency and large-scale fishing (LSF) over small-scale fishing (SSF) in policies and regulations, despite SSF’s importance for local resilience. While local actors seek to sustain the SSF industry, their participation in national decision-making is mainly symbolic. From this mismatch of national interests and local needs and weak political participation, SSF emerges as the loser regarding resilience-building efforts. Thus, strengthening local social resilience and adaptability requires the commitment of actors across scales to implement politically informed strategies.
Keywords: Social Resilience; Adaptation; Politics; Small-Scale Fisheries; Sustainability Science